Variability of mackerel fish catch and remotely-sensed biophysical controls in the eastern Pemba Channel. (15th June 2021) - Kizenga, Hellen J.; Jebri, Fatma; Shaghude, Yohana; Raitsos, Dionysios E.; Srokosz, Meric; Jacobs, Zoe L.; Nencioli, Francesco; Shalli, Mwanahija; Kyewalyanga, Margareth S.; Popova, Ekaterina
Abstract: Advances in satellite remote sensing of environmental perturbations have become important in understanding variations of ocean productivity and small pelagic fish catches. This marine resource is vital for coastal populations dependent on artisanal fishing for their income and food security, such as in coastal East Africa. In this region, the eastern Pemba Channel (Tanzania) represents a hotspot area, for a variety of marine species including small pelagics and coral reef associated species. This study examines the links between mackerel fish catch, one of the important small pelagic fish for direct consumption in the region, and changes in environmental oceanographic parameters over the period 2012–2018. The fisheries catch data is a rare local dataset, consisting of daily mackerel landings (from 2012 onwards) and supplemented by qualitative information on the mackerel fishery obtained through interviews with local stakeholders. The physical factors influencing phytoplankton biomass, and in turn, mackerel fisheries yield is investigated, using remotely-sensed chlorophyll-a ( Chl-a ) and Sea Surface Temperature (SST), together with Mixed Layer Depth (MLD) data from the high-resolution ocean model NEMO. We show that seasonal variations in mackerel landings are positively (negatively) correlated with Chl-a (SST) with a 1-month time lag (i.e., biophysical factors change first, mackerel stocks follow one month later). On the eastern side of the Pemba Channel, cooler SST and higher Chl-a are observed during the Southeast monsoon accompanied by increased mackerel landings, suggestive of enhanced productivity. Interannually, these relationships remain valid both for monthly and annual means, which confirms the close link between the variations of mackerel and biophysical conditions. Analysis of the Chl-a and MLD anomalies, relative to the mean, reveals that the phytoplankton blooms observed on the eastern side of the Pemba Channel, during the Southeast monsoon, are likely due to the deepening of the mixed layer, which tends to entrain cold and nutrient rich waters from greater depths to the surface. We conclude that upper ocean mixing contributes to the observed enhanced productivity along with other environmental factors. Additionally, we show how our results can be applied in the management of the mackerel resource in the Pemba Channel. Graphical abstract: Image 1